Sensitivity enhancement using anisotropic black phosphorus and antimonene in bi-metal layer-based surface plasmon resonance biosensor - Singh, Maneesh Kumar; Pal, Sarika; Verma, Alka; Mishra, Vimal; Prajapati, Yogendra Kumar (Superlattices and microstructures, 2021)
This work presents novel and highly sensitive Cu-Ni bimetallic surface plasmon resonance sensor based on hybrid structure of black phosphorus-antimonene for refractive index sensing of biomolecules. In this work, role of anisotropic BP for antimonene based bimetallic SPR biosensor is numerically investigated for the first time, using angular interrogation technique. First, the thicknesses of bimetals (Cu-Ni), number of BP layers and rotation angle phi for anisotropic BP based SPR structures were optimized to achieve the minimum reflectance. Then, performance factors are numerically evaluated at optimized parameters. This work achieves the highest angular sensitivity, i.e., 446.90°/RIU with optimum figure of merit than all other 2D nanomaterial based SPR sensor proposed till date. The anisotropic BP layers help to get the optically tuned ultrahigh sensitivity, making it promising SPR biosensor to explore highly anisotropic platforms for biosensing. •Bimetallic SPR biosensor based on anisotropic BP and antimonene is proposed.•Anisotropic BP layers can tune the sensitivity of SPR biosensor.•Highest sensitivity (446.9°/RIU) and figure of merit (93.10 RIU-1) are achieved for proposed anisotropic sensor.•Proposed anisotropic sensor outperforms among all SPR sensor proposed till date.